CORRELATION OF LEADERSHIP RESPONSIBILITY, REWARD GIVING, AND PROMOTION ON EMPLOYEE DEDICATION IN THE MINISTRY OF RELIGIOUS AFFAIRS OF THE RIAU ISLANDS PROVINCE - Magdalena Silfia; Risnita; Kemas Imron Rosadi (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the correlation between Leadership Responsibility, Reward Giving, and Promotion on Employee Dedication within the Ministry of Religious Affairs of the Riau Islands Province. This research employs a quantitative approach with a correlational method to determine the extent to which these three variables influence employee dedication both individually and simultaneously. The research sample was selected using cluster sampling, representing the central region (Karimun Regency), eastern region (Tanjungpinang City), and western region (Natuna Regency), totaling 72 respondents, of which 52 were used as the main sample and 20 as a trial sample. The findings indicate that leadership responsibility positively affects employee dedication, emphasizing the importance of leaders who provide clear guidance, foster effective communication, and create a work environment that supports motivation and performance. Reward giving is shown to enhance Employee Dedication by motivating them to achieve work targets and strengthening organizational loyalty. Meanwhile, promotion serves as a career incentive that encourages commitment and responsibility in task execution. Simultaneous analysis shows that these three variables collectively contribute significantly to improving employee dedication. These findings underscore that a combination of responsible leadership, an effective reward system, and transparent promotion policies can strengthen loyalty, commitment, and work ethic among employees in the Ministry of Religious Affairs. This study provides important implications for human resource management development in the public sector, particularly in strategies aimed at enhancing employee performance and dedication through appropriate managerial policies.